Dual NDP52 Function in Persistent CSFV Infection - Fan, Shuangqi; Wu, Keke; Luo, Chaowei; Li, Xin; Zhao, Mengpo; Song, Dan; Ma, Shengming; Zhu, Erpeng; Chen, Yuming; Ding, Hongxing; Yi, Lin; Li, Jun; et al. (Frontiers in Microbiology, 2020)
Abstract：Viruses have evolved many mechanisms to escape host antiviral responses. Previously, we found that classical swine fever virus (CSFV) infection induces autophagy using the autophagosome as a self-replication site, thereby evading the host immune response and promoting long-term infection. However, the underlying mechanisms used by CSFV to enter autophagosomes and the mechanism by which autophagy promotes viral replication remain unclear. We found that CSFV infection inhibited autophagy receptor nuclear dot protein 52 kDa (NDP52) expression, ubiquitination, and SUMO2-4 modification. Further analyses revealed that CSFV mediated ubiquitination and SUMOylation of NDP52 via PINK1-Parkin. Moreover, NDP52 inhibition also inhibited CSFV replication and the induction of mitophagy marker proteins expression. Inhibition of NDP52 reduced CD63 expression and binding to CSFV E2 protein, which has an essential role in persistent CSFV infection. As NDP52 has a close relationship with the NF-κB innate immunity pathway and plays an important role in the antiviral response, we investigated whether NDP52 inhibited CSFV replication through the release of immune factors and antivirus signals. Our results showed that inhibiting NDP52 boosted interferon and TNF release and promoted NF-κB pathway activation. In summary, we found that NDP52 inhibition not only reduces CSFV binding and entry into autophagic vesicles, but also inhibits CSFV replication by active NF-κB antiviral immune pathways. Our data reveal a novel mechanism by which NDP52, an autophagy receptor, mediates CSFV infection, and provide new avenues for the development of antiviral strategies.